The Future of Newborn Genomic Testing - John D. Lantos (MDPI AG, 2023)
Genome sequencing (GS) provides exciting opportunities to rapidly identify a diagnosis in critically ill newborns and children with rare genetic conditions. Nevertheless, there are reasons to remain cautious about the use of GS. Studies to date have been mostly in highly selected populations of babies with unusual clinical presentations. GS leads to diagnoses in many such infants. More rarely, it leads to beneficial changes in management. Parents and physicians whose babies meet these criteria and for whom GS is performed both find these results useful. The concern is this: we do not know how useful such testing will be in the general population. We can speculate that a number of problems will arise as the use of GS expands. First, the percentage of cases in which a valid molecular diagnosis is made will likely go down. The number of ambiguous results or false positives will rise. Genetic counseling will become more complex and challenging. We do not know the relative cost-effectiveness of whole genome, whole exome, or targeted panels in different populations. We do not know the relative contribution of a molecular diagnosis to the decision to withdraw life support. We will have to carefully evaluate the use of such testing in order to understand whether it truly improves outcome and survival or reduces symptoms in babies who are tested. Each of these concerns will require careful study of both the technology and the ethical issues to allow us to harness the potential of these new technologies while avoiding foreseeable problems. Studies are underway to see how the tests are used in general populations. These studies should generate important information to guide clinicians and policymakers. As part of informed consent, doctors should explain to parents that genetic results are not always straightforward. Sometimes, they confirm a diagnosis that was already suspected. Sometimes, they rule out a possible diagnosis. Sometimes, the results are ambiguous and difficult to interpret. Anticipatory discussions should try to give parents a realistic understanding of the likely impact of a genetic diagnosis. Diagnostic genomic testing for newborns is a science that is still in its infancy. More research is essential in order to establish how to personalize this promising but sometimes problematic tool.